If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = n + -3 Reorder the terms: 16 = -3 + n Solving 16 = -3 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 16 + -1n = -3 + n + -1n Combine like terms: n + -1n = 0 16 + -1n = -3 + 0 16 + -1n = -3 Add '-16' to each side of the equation. 16 + -16 + -1n = -3 + -16 Combine like terms: 16 + -16 = 0 0 + -1n = -3 + -16 -1n = -3 + -16 Combine like terms: -3 + -16 = -19 -1n = -19 Divide each side by '-1'. n = 19 Simplifying n = 19
| -2(-4x+1)+4x+5=-9 | | (7x-5yi)-(9-4i)=-2i+15 | | 16x^2-64x+48=0 | | c^2+7c+10=0 | | (2x+7)(x^2+2x-3)=0 | | -7c=-56 | | 2t-3t+8=3+-8 | | -1.25+.15x=0 | | 169=x^2+x^2+14x+49 | | 3x+5=-103-9x | | h=-16t^2+96t+4 | | 64b^2-121=0 | | 156-6x=3x+21 | | 4+6x-9x=3x | | b^2-4=0 | | 0.3b=8.1 | | 45x^6+18x^4-80x^2-32=0 | | -3z=72 | | 5x^2+19x-30=0 | | -5x+4(-5x+1)=129 | | 360=-18n | | 68-6x=9x+23 | | 8m^2-10m-3=0 | | b=9(1-b) | | 4c^2+15c-4=0 | | 6x+6=86-2x | | 48=16x | | 5y(y)(5y-1)+(2)5y-1= | | 15x=-225 | | 12x^3-38x+26=0 | | 15x=-132 | | 17lb=102 |